Pesquisa dos genes icaD e bap de adesão intercelular bacteriana e formação de biofilme por Staphylococcus aureus e Staphylococcus coagulase-negativa isolados de mastite bovina - Salina, Anelise [UNESP] (2015)
Staphylococcus aureus is common in intramammary infections, which often become chronic, among other factors, by the ability of this bacteria to produce biofilm. The objective was to verify the production of biofilm capacity in strains of S. aureus and coagulase negative Staphylococcus (CNS), derived from clinical and subclinical bovine mastitis. A total of 100 strains of S. aureus and 100 strains of CNS were isolated from cases of subclinical and clinical mastitis in two properties of São Paulo State. The screening test of subclinical mastitis was the California Mastitis Test (CMT). Somatic Cell Count (SCC) and microbiological culture of milk samples was performed. We researched the presence of icaA, icaD and bap genes by the Polymerase Chain Reaction (PCR) and phenotypic characterization on congo red agar (CRA) and biofilm production on plates. There was no observed relationship between the intensity of the reaction to the CMT and SCC. The mean of SCC was 2.88 ± 0.59 for S. aureus and 2.71 ± 0.35 for CNS. There was no significant statistical between SCC values for strains containing the presence of those researched genes. But the means of the CCS values were higher in isolates that containing such genes. The frequency icaA, icaD and bap in S. aureus were 82%, 83% and 58%, respectively. It was observed that the 83% of S. aureus isolates that had icaD, 82 (98.8%) also had icaA, with statistical significance in the Fischer's exact test (p <0.001). In association between icaA and bap genes, was also observed significant association, for the 82 strains that showed icaA, we observed the presence of bap in 56 (68.3%). Of the 83 strains that containing the icaD gene, 56 (67.5%) of them was also detected the presence of bap gene. There was no agreement between the phenotypic tests (K<0.2). The positivity on congo red agar revealed that 25% of S. aureus strains produced in vitro biofilm. In the adhesion test plates, this number was lower, with ...